More than a digestive disorder: Perceived stigma in inflammatory bowel disease patients - Neslihan Güneş Aydemir; Ali Çağrı Oral; Tuğçe Taşar Yıldırım (PLoS ONE, 2026)
Background Inflammatory bowel disease (IBD) is a chronic condition characterized by symptoms that are often difficult to conceal and may expose patients to negative social reactions. Beyond physical burden, stigma represents an important but underrecognized psychosocial challenge in IBD, potentially affecting social functioning and disease management. To determine the prevalence of perceived stigma among patients with IBD and to evaluate its association with disease subtype, sociodemographic characteristics, clinical features, and self-esteem. Methods A total of 146 patients with IBD under regular follow-up were included in this cross-sectional study. Perceived stigma was assessed using ten disease-specific yes/no items reflecting real-life stigma-related experiences. Sociodemographic data, clinical characteristics, and self-esteem levels measured by the Rosenberg Self-Esteem Scale were recorded. Patients were classified as experiencing stigma if they endorsed at least one stigma item. Results Overall, 63.0% of patients reported at least one stigma-related experience. The most frequently reported manifestations were social avoidance and discomfort in public settings, while overt discrimination was less common. The distribution of stigma-related experiences was largely similar between Crohn’s disease and ulcerative colitis patients. Individuals reporting stigma were significantly younger and had a younger age at diagnosis compared to those without stigma. No significant differences were observed with respect to gender, marital status, education, employment, income, disease subtype, surgical history, or comorbidities. Patients experiencing stigma had significantly lower self-esteem scores than those without stigma. Conclusion Perceived stigma is common among patients with IBD, particularly among younger individuals, and is more often expressed as social discomfort and avoidance rather than explicit discrimination. These findings highlight stigma as an important psychosocial dimension of IBD that warrants greater clinical attention. Integrating psychosocial support into routine care may help mitigate stigma-related consequences and improve overall disease management. Longitudinal studies are needed to clarify the long-term impact of stigma on disease outcomes.